The Influence of Dongklak Dance Learning on the Perception of Students at the Indonesian School of Kuala Lumpur (SIKL) Regarding Indonesian Culture - Nabila, Jihan; Winarti, Puji; Legowo, Yogi Ageng Sri (Riwayat: Educational Journal of History and Humanities, 2025)
Indonesia is known for its social diversity, which includes ethnicities, cultures, religions, and customs. The principle of "Bhineka Tunggal Ika" reflects the spirit of unity in diversity, despite significant differences. Cultural changes in Indonesia are influenced by globalization, which accelerates shifts in traditions, especially among the younger generation, particularly Indonesian children living abroad. These children often struggle to understand Indonesian culture due to limited exposure to cultural education. This study aims to explore how Dongklak Dance learning influences students' perceptions of Indonesian culture at the Indonesian School of Kuala Lumpur (SIKL). Dongklak Dance, originating from East Java, embodies values of cooperation, togetherness, and mutual assistance, and is expected to introduce students to the richness of Indonesian culture and strengthen their emotional connection to their cultural identity. The results of the study indicate that Dongklak Dance learning has a positive impact on students' perceptions of Indonesian culture, enhancing their pride and understanding of national traditions.